ATAP HIJAU - Sebuah Kajian Asimilasi Budaya Berkebun dan Bermukim pada Rumah Tropis - Sri Yuliani (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
At present the portrait of land use in several cities is dominated by settlements or dwellings. Settlements in tropical climates have the potential to support the environment for thriving plants. Therefore, research that is oriented to optimizing the tropical climate in the settlement sector is very important because in the science of architecture designing buildings is very necessary to consider the harmony of buildings, climate and humans. The culture of Indonesian society from generation to generation is a tradition that needs to get space side by side with the fulfillment of residential needs. Gardening culture is an effort to meet food needs, while living culture is an effort to meet the needs of the board, so that both are primary human needs. The research objective is to study the prospect of the assimilation of the culture of gardening and living through quantitative and qualitative paradigms. The focus of the study determined the relationship between the two variables with statistical analysis through the correlation of people's appreciation of gardening activities with income level, in the statistical test analysis using the chi square method. The results of the quantitative analysis continued with efforts to find reasons for causal relationships through in-depth interviews. The results of the study concluded that there was a correlation between the appreciation of the community and the level of income in supporting the assimilation of the culture of gardening and living in tropical homes. The problem of limited land is the cause of the lack of assimilation of the culture of gardening and living in low-income communities.